Screening for lactic acid bacteria in traditional fermented Tibetan yak milk and evaluating their probiotic and cholesterol-lowering potentials in rats fed a high-cholesterol diet. (May 2017) - Ding, Wurong; Shi, Chao; Chen, Ming; Zhou, Jianwei; Long, Ruijun; Guo, Xusheng
Highlights: Cholesterol-lowering effects of LAB isolates from yak yoghurt were investigated. L. plantarum LP3 was screened out due to its high cholesterol-lowering activity. The strain exhibited an excellent tolerance to simulated GI tract. It effectively alleviated the hyperlipidemia in rats fed a high-cholesterol diet. The strain could be a potential probiotics to be used in functional food. Abstract: The objectives of the present study were to screen cholesterol-lowering lactic acid bacteria from traditional fermented Tibetan yak milk, and to evaluate their potential use as cholesterol-reducing probiotics in rats. A total of 115 isolates were evaluated for their cholesterol-lowering and probiotic profiles by in vitro assays, and a strain with good performance in in vitro test was selected to test its probiotic effects in rats fed a high cholesterol diet. Results showed that the strain of L. plantarum Lp3 had a high cholesterol-reducing rate (73.3%) and survival rate in simulated gastrointestinal fluids. Administration of Lp3 to rats fed a high-cholesterol diet promoted notable declines in serum and liver cholesterol and triglycerides levels, and reduced lipid deposition in the cytoplasm of rat's liver tissue. These results suggest that the strain of L. plantarum Lp3 could be a potential probiotic to treat hyperlipidemia and to be used in functional food.